When Refugees are Women: Emergence of the Issue on the International Agenda - Osaki, Keiko (Refuge: Canada's Journal on Refugees, 1997)
Using the latest refugee statistics availablefrom the United Nations HighCommissionerfor Refugees (UNHCR),the author examines, first, the presenceof women in refugee populations. Second,she chronologically reviews the efforts of the United Nations and UnitedNations agencies to heighten awarenessregarding the issue, and to resolve specificproblems that refugee women face.Lastly, the special needs for women refugeesare identified with implications forpossible program interventions.